w-Functions in Topological Spaces - Massuodah Saad Tarjam; Khairia Mohamed Mira; Khadiga Salem Abdeen (African Journal of Advanced Pure and Applied Sciences, 2025)
The purpose of this research is to explore the properties of w-open sets and extend the concepts of interior and closure operators through these sets. Furthermore, we define new classes of functions in topological spaces, such as w-continuous, w-irresolute, w-open, and w-closed functions, and analyzing their characteristics and the relationships between them.